Short-Interval Sequential CAR-T Cell Infusion May Enhance Prior CAR-T Cell Expansion to Augment Anti-Lymphoma Response in B-NHL - Meng, Yuan; Deng, Biping; Rong, Luan; Li, Chuo; Song, Weiliang; Ling, Zhuojun; Xu, Jinlong; Duan, Jiajia; Wang, Zelin; Chang, Alex H.; Feng, Xiaoming; Xiong, Xiujuan; et al. (Frontiers in Oncology, 2021)
Chimeric antigen receptor (CAR) T-cell therapy is a new promising treatment for refractory or relapsed (r/r) B-cell non-Hodgkin lymphoma (B-NHL), and has been widely used in recent years. However, the overall response rate (ORR) is much lower in B-NHL than in r/r B acute lymphoblastic leukemia (B-ALL) patients. Sequential infusion of CD22 CAR-T after responding to prior CD19 CAR-T therapy improved the complete remission (CR) rate of B-NHL reported by our group, while there were still some advanced patients who had progression during CD19 CAR-T therapy and failed the treatment. In this study, We hypothesize the co-expansion of different CAR T-cells contributes to enhanced anti-tumor effects. The modified sequentially infused CAR T-cells after initial treatment had significant advantages on the amplification of the prior CAR T-cells, along with stronger tumor-killing capacity. We further conducted compassionate treatments on two patients with advanced B-cell lymphoma by modified sequential infusion of different CAR T-cells. Disease progression was observed in both patients after single CD19 CAR T-cell infusion and enhanced anti-tumor effects which caused by co-expansions of different CAR T-cells reversed the tide and finally induced CR. Clinical trials with modified infusion strategy will be conducted for further verification.